1993
DOI: 10.1007/bf00184363
|View full text |Cite
|
Sign up to set email alerts
|

Das inguinale Rezidiv nach therapeutischer Lymphadenektomie beim malignen Melanom

Abstract: In a retrospective study, 73 stage-II melanoma patients with 22 superficial and 51 deep groin dissections were observed over a maximum of 9 years of follow up (median 67.5 months). The 5-year survival rate of 29.8% was consistent with that yielded by comparable analyses of other investigators. However, the probability of recurrence in the node dissection field was as high as 35%. All groin recurrences occurred in the first 29 months after lymph node clearance (median 6 months). Patients with groin recurrence f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Moreover, local recurrence in itself has a poor prognosis. We have previously demonstrated that the prognosis after recurrence in the dissected axilla is comparable with the prognosis of stage IV melanoma [18].…”
Section: Intransit Metastases and Local Recurrencementioning
confidence: 92%
See 2 more Smart Citations
“…Moreover, local recurrence in itself has a poor prognosis. We have previously demonstrated that the prognosis after recurrence in the dissected axilla is comparable with the prognosis of stage IV melanoma [18].…”
Section: Intransit Metastases and Local Recurrencementioning
confidence: 92%
“…An improvement of local disease control by the application of surgical standard techniques might also have been expected in malignant melanoma but have not been previously demonstrated for patients with axillary lymph node metastases. In a previous paper [18], we had reported a local recurrence rate of 35 per cent after the excision of palpably enlarged axillary nodes. As a consequence, an operative procedure according to established standard techniques [3,11] was introduced in our clinic thereafter, and we now want to reassess whether the introduction of standardized lymphadenectomy has led to improved local control or survival rate.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Kissin et al [25], Singletary et al [3], Kretschmer et al [26], Harman et al [24], Mann and Coit et al [4], and Hughes and Thomas [1] observed more recurrences in the groin and pelvis after superficial dissection alone. Differences are found in general between a superficial (inguinal) and a combined inguinal and pelvic dissection.…”
Section: Discussionmentioning
confidence: 99%